PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SD NEGERI 3 BUDAKELING TAHUN PELAJARAN 2025/2026 - I Komang Suardiana; Ni Kadek Depi Dumaini; Gusti Ayu Nanik Ardhiani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted in response to the low IPAS learning outcomes of fourth-grade students at SD Negeri 3 Budakeling in the 2025/2026 academic year. The study aimed to improve the IPAS learning outcomes of these students by implementing the Group Investigation type of cooperative learning model assisted by Wordwall media. This study employed a Classroom Action Research (CAR) design consisting of two cycles. Each cycle included four stages: planning, action implementation, observation, and reflection. Subjects were 27 fourth-grade students of SD Negeri 3 Budakeling in the 2025/2026 academic year, consisting of 13 boys and 14 girls. Findings revealed that the implementation of the Group Investigation cooperative learning model significantly improved the students' IPAS learning outcomes. Before intervention, the pre-cycle results showed a mean score of 65.77, a learning absorption rate of 65.77%, and a learning mastery level of 48.15%. After the implementation of Cycle I, mean score increased to 73.51, the learning absorption rate reached 73.51%, and the learning mastery level improved to 74.07%. The students' learning outcomes improved further after Cycle II, achieving a mean score of 81.67, a learning absorption rate of 81.67%, and a learning mastery level of 96.29%. The Minimum Learning Achievement Criteria (KKTP) was set at 70, while the required level of classical learning mastery was 85%. Based on the data analysis and discussion, study concludes that implementing Group Investigation type of cooperative learning model effectively improved the IPAS learning outcomes of fourth-grade students at SD Negeri 3 Budakeling in the 2025/2026 academic year.